Nanoparticles and the immune system. - Ghosh, Shyamasree (De Gruyter, 2022)
"The fast development in the field of nanotechnology has led to a high variety of nanoparticles. Nanoparticles find importance in every sphere of human lives and more so in the recent years have tremendous applications in the sector of biomedical clinical medicine as diagnostic, prognostic and imaging tools. Their risk to human and animal life as well as to the environment is still unclear. Therefore, the study of the impact of nanoparticles on human and animal life is important. Volume I highlights the impact of nanoparticles on the human immune system. While discussing the basic biology of the immune system, this book highlights the downstream effect of nanoparticles on the human immune system. Research studies on the development of better and more effective nanoparticles with more precise and accurate effects and with toxic minimal side effects are discussed in the book. Both volumes are also included in a set ISBN 978-3-11-065666-4."--